2021
DOI: 10.1007/s00380-021-01770-w
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular global longitudinal strain in predicting CRT response: one more J-shaped curve in medicine

Abstract: The aim of the study was: (1) to verify the hypothesis that left ventricular global longitudinal strain (LVGLS) may be of additive prognostic value in prediction CRT response and (2) to obtain such a LVGLS value that in the best optimal way enables to characterize potential CRT responders. Forty-nine HF patients (age 66.5 ± 10 years, LVEF 24.9 ± 6.4%, LBBB 71.4%, 57.1% ischemic aetiology of HF) underwent CRT implantation. Transthoracic echocardiography was performed prior to and 15 ± 7 months after CRT implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…10 Several studies reported baseline global longitudinal strain predicts LV reverse remodeling after CRT in patients with both ischemic and non-ischemic cardiomyopathy. [11][12][13] In our study strain parameters have also significantly improved.…”
Section: Discussionmentioning
confidence: 52%
“…10 Several studies reported baseline global longitudinal strain predicts LV reverse remodeling after CRT in patients with both ischemic and non-ischemic cardiomyopathy. [11][12][13] In our study strain parameters have also significantly improved.…”
Section: Discussionmentioning
confidence: 52%
“…The most common definition of CRT response is that the patient has fewer symptoms and/or better clinical outcomes with this therapy than without it. Interestingly, the most commonly used criterion for CRT efficacy is not LVEF improvement (such as in the assessment of HFimpEF) but LVESV reduction by >15%, because it corelates more accurately with long-term survival in CRT recipients [ 72 , 73 ]. Moreover, there is no defined time frame for CRT assessment.…”
Section: Cardiac Implantable Electronic Device and Hfimpefmentioning
confidence: 99%